CHILDHOOD UNINTENTIONAL INJURY PREVENTION IN JOHNSON COUNTY, KANSAS - Marshall, Clara (My University, 2013)
Unintentional childhood injuries are a largely unrecognized and underfunded problem in public health. The burden of childhood injury in mortality and morbidity relative to that of infectious disease has been growing steadily over the past few decades. Prevention efforts are disconnected and competing messages abound, confusing children, parents, and caregivers about safety practices. There is also a dearth of research into the effectiveness of injury prevention strategies, making the implementation of evidence-based interventions difficult. The purpose of this project was the creation of educational presentation materials for health educators serving Charlie’s House, a nonprofit organization dedicated to preventing childhood injuries in the greater Kansas City area. This was accomplished through a review of journal articles and online materials pertinent to childhood injury prevention strategies and interventions, as well as the inclusion of input of content experts. The main unintentional injury risks to children are motor vehicle accidents, where children are injured as passengers, cyclists, and pedestrians; drowning; fires and burns; suffocation; and poisoning. Injury morbidity and mortality risks are further stratified by age: children under 1 year old tend to die from unintended suffocation or accidental strangulation; children aged 1-4 are most likely to die from drowning; and older children mostly die from traffic injuries, as occupants, pedestrians, or cyclists. Educational materials were designed to be compelling, accessible, and modifiable to fit the needs of diverse audiences. As the foundation of much of public health, education is a valuable tool to inform the public about potential risks and safety measures, and can help change attitudes and behaviors. This, in turn, can create a community culture of safety and heighten awareness of the environmental and policy changes needed to effectively protect children from unintentional injuries.
Keywords: Public Health; Childhood injury prevention; Johnson County Kansas; Public Health (0573)